ANALISIS KARAKTERISTIK KELUARGA SISWA YANG MEROKOK KELAS XI SMA NEGERI 5 TANAH PUTIH - Maria '; Zulfan Saam Zulfan Saam; Tri Umari Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract was based on observation that was carried out by the writer through the poll took the form of the scale, then most students in the SENIOR HIGH SCHOOL smoked. The aim of this research was: (1) To know the characteristics of the level of education, the level of economics, and the work kind of parents from the student that smoked (2) To know the behaviour of parents towards the behaviour of the student that smoked. The method that was used in this research was the method deskriktif that is this research aimed at making the description (pencitraan) systematically, factual accurate concerning facts and sipat-sipat the population or certain areas. The population was keselurauahan the object or the subject of the research. In this research the writer's population was all the student the Negeri SENIOR HIGH SCHOOL 5 Putih Yang lands smoked. Whereas that was meant by the sample to be part of the representative population this population. In this research the taking of the sample was carried out by means of making all the population become the sample, because of the number of populations not many, then all the population was made the sample (the bored sample).Was based on results of data processing then results of the research were as follows: the characteristics of the level of parents's education for the student that smoked in the SENIOR HIGH SCHOOL is generally the level of low education in fact more than half of the father's education SDTT and hamper half of the mother's education also SDTT, Kateristik the level of parents's economics of the student that smoked was sebagain big the category ekomoni low, only sebagain just small the level ekomoni high, the characteristics of the work kind of parents of the student that smoked was most works of the father of being the farmer and the mother was as the housewife, the Behaviour of parents towards the behaviour of the student that smoked was the child was allowed to work personally to receive money to buy cigarettes, the child smoked outside the house without the controlling of parents, the shortage of the feeling of attention of parents to the health of the child when the child of coughs, the student who smoked his parents also smoked. The recommendation from this research was for the student that smoked in order to not work dipagi the day at the school hour, for the student that smoked so that did not smoke in the school environment, for parents of the student in order to be able to give attention and the love loved the child, for parents of the student that smoked so that did not smoke in front of the child and did not smoke together with the child. The key word: the characteristics of the family and the student that smoked